2006
DOI: 10.1037/0735-7028.37.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the validity and utility of criminal profiling among forensic psychologists and psychiatrists.

Abstract: Criminal profiling is the process of using crime scene evidence to make inferences about potential suspects, including personality characteristics and psychopathology. An exploratory Internet survey of forensic psychologists and psychiatrists was conducted to examine their experiences with and opinions about profiling and to determine whether referring to profiling as "criminal investigative analysis" had any impact on these opinions. About 10% of the 161 survey respondents had profiling experience, although m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…Bartol (1996) found that 70% of the surveyed police psychologists seriously questioned the validity of profiling as a discipline. This finding was almost perfectly mirrored in the subsequent study conducted by Torres, Boccaccini, and Miller (2006) into the perception of profiling among forensic psychologists and psychiatrists. Yet, despite the negative impressions harboured by the surveyed practitioners regarding the reliability of profiling, the vast majority admitted to its utility in the law enforcement context.…”
Section: Validity Measurement Dilemmasupporting
confidence: 52%
See 1 more Smart Citation
“…Bartol (1996) found that 70% of the surveyed police psychologists seriously questioned the validity of profiling as a discipline. This finding was almost perfectly mirrored in the subsequent study conducted by Torres, Boccaccini, and Miller (2006) into the perception of profiling among forensic psychologists and psychiatrists. Yet, despite the negative impressions harboured by the surveyed practitioners regarding the reliability of profiling, the vast majority admitted to its utility in the law enforcement context.…”
Section: Validity Measurement Dilemmasupporting
confidence: 52%
“…Yet, despite the negative impressions harboured by the surveyed practitioners regarding the reliability of profiling, the vast majority admitted to its utility in the law enforcement context. An explanation advanced by Torres et al (2006) for this apparent paradox is that the perception of utility of profiling may be strongly influenced by its ever-growing use. Woskett, Coyle, and Lincoln (2007) sought the opinions that lawyers held of profiling.…”
Section: Utility Investigative Relevance and Consumer Satisfactionmentioning
confidence: 99%
“…The older term offender profiling has developed an almost mythic status in popular literature and drama (Herndon, 2007), although, as this paper will demonstrate, in its best understood but narrow definition, it has failed to make much operational impact. Moreover, several studies have shown that the idea of psychologists being able to generate a coherent set of offender characteristics by inferring latent patterns or ‘styles’ of offending from crime scene information has proven empirically and theoretically problematic (see Snook, Cullen, Bennell, Taylor, & Gendreau, 2008), although they themselves recognize some recent and notable exceptions (e.g. Goodwill & Alison, 2007; Goodwill, Alison, & Beech, 2009; Mokros, 2007; Santtila, Pakkanen et al , 2008) as the field has developed.…”
mentioning
confidence: 99%
“…The two main study domains were originally identified in the published literature: knowledge (Ali et al, 2016, Bhakhri et al, 2017, Sahni et al, 2016) and perception (Astekar et al, 2011, Bhakhri et al, 2017, Stow and Higgins, 2018, Torres et al, 2006). The knowledge domain questioned the participants about the general benefits of forensic odontology and the significance of its use.…”
Section: Methodsmentioning
confidence: 99%